Mapping Research Trends on the Culturally Responsive Transformative Teaching (CRTT) Learning Model to Improve Critical Thinking Skills - Ryya Aulia Assirri; Nisa Hidayatullah; Riska Dia Sapitri; Rizka Sofia Irawan; Sri Suci Lestari (Balai Publikasi Indonesia, 2026)
This study aims to map research trends on the Culturally Responsive Transformative Teaching (CRTT) learning model in an effort to improve students' critical thinking skills from 2016–2025. The study was conducted through bibliometric analysis using data obtained from Google Scholar, processed with Publish or Perish, Dimensions.ai, and visualized using VOSviewer. A total of 200 documents were analyzed using the PRISMA flow to identify publication developments, source types, citations, and keyword relationships. The results show that the CRTT research trend has increased significantly in the last decade, with a dominance of scientific articles and an increase in citations on topics related to science learning, ethnoscience, cultural literacy, and the development of critical thinking skills. Keyword analysis revealed that terms such as curriculum, century skill, STEM, action, and lesson study have become important focuses in the development of CRTT. Network and overlay visualizations show a shift in research from conceptual studies to contextual implementation based on local culture and technology integration. These findings confirm that CRTT is a relevant pedagogical approach for building transformative, culturally responsive learning, and is effective in developing students' critical thinking skills in various educational contexts. This study provides a foundation for further research as well as practical recommendations for implementing the CRTT model in schools and developing a culture-based curriculum